POLA KONSUMSI RUMAH TANGGA TANI DI DESA HABI KABUPATEN SIKKA - Fiator Nong (Agriculture - Jurnal Ilmu Pertanian, 2022)
Food is a basic need that must be met by every human being. Nutritional Status Assessment can be used as a basis for developing community and national programs to help overcome malnutrition, provide the amount and type of food needed and generally support the health of the population. Sikka Regency, in general and Kangae District in particular have diverse agro-ecosystem areas that produce various types of commodities that can be consumed. This means that food diversification or diversification to support community food security can continue to be developed starting from the production aspect, processing aspect, distribution aspect to the aspect of food consumption at the individual or household level. The research was conducted in Habi Village, Kangae District, Sikka Regency, from May to September 2021. The results of the study showed that the consumption of the residents of Habi Village had not met the ideal balance and diversity standards, and the quality of food consumption of the Habi Village community had not met the Nutritional Adequacy Rate (AKG) standard. Therefore, it is necessary to make efforts to accelerate locally-based food diversification as a whole and increase public awareness and understanding of the importance of food consumption patterns.